Lumutinines A-D, linearly fused macroline-macroline and macroline-sarpagine bisindoles from alstonia macrophylla - Lim, Siew-Huah; Tan, Shin-Jowl; Low, Yun-Yee; Kam, Toh-Seok (2010)
Four new linearly fused bisindole alkaloids, lumutinines A D (1-4), were isolated from the stem-bark extract of Alstonia macrophylla. Lumutinines A (1) and B (2) represent the first examples of linear, ring A/F-fused macroline-macroline-type bisindoles, while lumutinines C (3) and D (4) were constituted from the union of macroline and sarpagine moieties. A reinvestigation of the stereochemical assignment of alstoumerine (8) by NMR and X-ray diffraction analyses indicated that the configuration at C-16 and C-19 required revision.